Causes and Features of Childhood Trauma in COVID-19 Period - Narsat, Mehmet Ali (Journal of Maternal and Child Health, 2021)
Background: In this study, we aimed to reveal the characteristics and severities of child traumas under the Covid-19 pandemic and lockdown according to trauma mechanisms, locations and age distributions, and to evaluate the results. Subjects and Method: The data of 333 pediatric trauma patients who came to our hospital during the lockdown period were analyzed retrospectively. The frequency and ratio analysis of the data obtained by the purposeful sampling method was performed. Pediatric Trauma Score, Injury Severity Score and Pediatric Glasgow Coma Scale were calculated. Gender, age distribution, trauma locations and trauma mechanisms were recorded, and distribution characteristics of the data according to trauma scores were compared. Continuous variables were analyzed using Student's t-test. Categorical variables were analyzed using the chi-square test. Statistical significance level was accepted as <0.05. Results:193 of the patients (58.0%) were male. The mean age of the patients was 7.73 (Mean= 7.73; SD= 5.33). The most common trauma patients (49.8%) consisted of the school age patients. The number of patients who applied to our hospital from the urban was 244 (73.3%), and it was observed that the trauma occurred at homeside in 189 (56.8%) patients. The most common cause of trauma was falls. The mean Pediatric Trauma Score of the patients was 10.43 (Mean= 10.43; SD= 1.28), the Injury Severity Score was 2.24 (Mean= 2.24; SD= 4.45), the Pediatric Glasgow Coma Scale calculated was 14.95 (Mean= 14.95; SD= 0.66). It was observed that 99.7% of the study patients according to the Injury Severity Score and 93.7% according to the Pediatric Trauma Score were minor trauma. Conclusion: Major childhood traumas and mortality decreased with the Covid 19 pandemic and lockdown. Keywords: Childhood, Covid-19, Pediatric Trauma Score, Injury Severity Score, Pediatric Glascow Coma Scale Correspondence: